The Evaluation of Digital Scrapbook Among Middle School Students - Efendi, Silvina; Berlian, Mery; Vebrianto, Rian (Universitas Pendidikan Indonesia, 2023)
Digital scrapbook is a learning media alternative that can be used as an educational medium. In addition to increasing motivation and interest in learning junior high school students and optimizing the division of labor in groups, this media was developed to avoid abstract thinking, a negative impression that is allowed to occur since they are tiny, which ends until adulthood the negative impression is bland and makes students bored. Studies related to developing instruments to measure digital scrapbooks as educational media use among tertiary institutions still need to be completed. This study aims to provide exciting education to junior high school students in science subjects, especially environmental pollution. Researchers used the research and development model Borg and Gall.